Distillation control: an engineering perspective - Smith, Cecil L (Wiley, 2012)
"Today, distillation is by far the most common separation technique used in the chemical and petroleum industries. Distillation Control approaches this subject from a process engineering perspective to explain the use of steady-state simulations to develop, to analyze, and to troubleshoot all aspects of column controls, including their practical application and cost benefits. Practicing engineers and other professionals working in process facilities that use distillation to separate materials will find this book a reliable companion"-- Provided by publisher "This book approaches the subject from a process engineering perspective, specifically, to use the steady-state simulation of the column as the primary source of the parameters required to develop, to analyze, and to troubleshoot a column control configuration. For an operating column, the first action must be to confirm that the separation currently provided by the column is consistent with design expectations (using control sophistication to solve process problems is a loser). The objective is to choose the control configuration that properly reflects the column design parameters (number of stages; feed stage location, etc), the materials being separated (relative volatility), the operating requirements for the column (reflux ratios, product purities, etc)"-- Provided by publisher